Glucosylation of flavonoids and flavonoid glycosides by mutant dextransucrase from Lactobacillus reuteri TMW 1.106. (1st September 2019) - Klingel, Tizian; Hadamjetz, Martina; Fischer, Anja; Wefers, Daniel
Abstract: Flavonoids are commonly abundant, plant-derived polyphenolic compounds which are responsible for color, taste, and antioxidant properties of certain plant based foods. Glucosylation by glucansucrases or other glycosyltransferases/glycoside hydrolases has been described to be a promising approach to modify stability, solubility, bioavailability, and taste profile of flavonoids and other compounds. In this study, we modified and applied a recombinant dextransucrase from Lactobacillus reuteri TMW 1.106 to glucosylate various flavonoids and flavonoid glycosides. The glucoconjugates were subsequently isolated and characterized by using two-dimensional NMR spectroscopy. Efficient glucosylation was achieved for quercetin and its glycosides quercetin-3- O -β-glucoside and rutin. Significant portions of α-glucose conjugates were also obtained for epigallocatechin gallate, dihydromyricetin, and cyanidin-3- O -β-glucoside, whereas glucosylation efficiency was low for naringin and neohesperidin dihydrochalcone. Most of the flavonoids with a catechol or pyrogallol group at the B-ring were predominantly glucosylated at position O 4'. However, glycosyl substituents such as β-glucose, rutinose, or neohesperidose were glucosylated at varying positions. Therefore, mutant dextransucrase from L. reuteri TMW 1.106 can be applied for versatile structural modification of flavonoids. Graphical abstract: Image 1 Highlights: Multiple flavonoids were glucosylated by using a mutant L. reuteri dextransucrase. The B-ring of different flavonoids was preferably glucosylated at position O 4. Flavonoid-bound glucose units were glucosylated at varying positions. Rutinose and neohesperidose units were glucosylated at position O 4 of rhamnose. Glucosylation positions and extent greatly depend on the structure of the substrate.